CULTURE RESEARCH IN THE RECENT WORK OF ITAMAR EVEN-ZOHAR - Harry Aveling (Soegijapranata Catholic University, 2008)
Even-Zohar is highly regarded among scholars of Translation Studies for his theoretical contributions in the area of